2016
DOI: 10.1182/blood-2016-06-725366
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and adult progenitors give rise to unique populations of CD8+ T cells

Abstract: During the ontogeny of the mammalian immune system, distinct lineages of cells arise from fetal and adult hematopoietic stem cells (HSCs) during specific stages of development. However, in some cases, the same immune cell type is produced by both HSC populations, resulting in the generation of phenotypically similar cells with distinct origins and divergent functional properties. In this report, we demonstrate that neonatal CD8 T cells preferentially become short-lived effectors and adult CD8 T cells selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(131 citation statements)
references
References 57 publications
5
126
0
Order By: Relevance
“…We first asked whether CD8 + T cells from different developmental origins exhibit unique phenotypes in the periphery of adult mice. Previous studies (Akue et al, 2012;Wang et al, 2016) indicated that uninfected neonatal mice contain a large fraction of ''virtual memory'' (VM) cells, which are naive CD8 + T cells that acquire phenotypic markers (CD44 and CD122) and functional properties (rapid response to stimulation) akin to memory CD8 + T cells. However, VM cells are produced by homeostatic mechanisms and arise in the absence of foreign antigen.…”
Section: Cd8 + T Cells Made Early In Life Have An Inherent Propensitymentioning
confidence: 99%
See 1 more Smart Citation
“…We first asked whether CD8 + T cells from different developmental origins exhibit unique phenotypes in the periphery of adult mice. Previous studies (Akue et al, 2012;Wang et al, 2016) indicated that uninfected neonatal mice contain a large fraction of ''virtual memory'' (VM) cells, which are naive CD8 + T cells that acquire phenotypic markers (CD44 and CD122) and functional properties (rapid response to stimulation) akin to memory CD8 + T cells. However, VM cells are produced by homeostatic mechanisms and arise in the absence of foreign antigen.…”
Section: Cd8 + T Cells Made Early In Life Have An Inherent Propensitymentioning
confidence: 99%
“…However, a number of recent studies have demonstrated that some naive CD8 + T cells possess different cell-intrinsic properties prior to their response to infection, which influence their kinetics and phenotypes after infection (Reynaldi et al, 2016;Smith et al, 2014;Wissink et al, 2015). In particular, neonatal CD8 + T cells derived from fetal liver hematopoietic stem cells (HSCs) are inherently more proliferative and have an enhanced capacity to differentiate, when compared to CD8 + T cells produced from adult bone marrow HSCs later in life (Wang et al, 2016). Similar results have also been described for fetal-derived CD4 + T cells in mice (Adkins et al, 2003;Zens et al, 2017) and humans (Mold et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors transplanted a timestamped neonatal thymus into a timestamped adult mouse and T cells derived from the neonatal thymus contained a comparable frequency of T VM cells to an intact neonate, despite having emerged into a lymphoreplete environment . Additionally, after intrathymic transfer into adults, double‐negative (DN) thymocytes sourced from mouse fetuses preferentially develop into T MP , likely T VM , cells as compared to DN thymocytes from adult mice . The expression of an RNA‐binding protein called Lin28b, which is known to control pluripotency, appears to contribute to preferential T VM ‐cell development.…”
Section: Refining the Model Of Tvm‐cell Generationmentioning
confidence: 99%
“…22 Additionally, after intrathymic transfer into adults, double-negative (DN) thymocytes sourced from mouse fetuses preferentially develop into T MP , likely T VM , cells as compared to DN thymocytes from adult mice. 33 The expression of an RNA-binding protein called Lin28b, which is known to control pluripotency, appears to contribute to preferential T VM -cell development. These pivotal experiments clearly illustrate that a form of programming occurs during the development to dictate the fate of T cells in the periphery.…”
Section: Refining the Model Of T Vm -Cell Generationmentioning
confidence: 99%
“…In murine acute infection models, neonatal CD8 T cells terminally differentiate and form a reduced memory pool, whereas adult CTLs demonstrate a bifurcation of their response representing both a terminally differentiated and memory pools. There are two primary theories regarding why neonatal CD8 + T cells assume different end results from adults during infection: the proliferation model and the origin model . The proliferation model dictates that variations in the CD8 + T‐cell response during development are the result of differences in homeostatic proliferation prior to infection.…”
Section: Development Of the Memory Cd8+ T‐cell Compartmentmentioning
confidence: 99%